Pengunaan Media Ban Terhadap Peningkatan Kemampuan Pointing Pada Atlet Petanque Kabupaten Kuburaya - Anjeli; Fallo, Ilham Surya; Sabransyah, Mohammad (IKIP PGRI Pontianak, 2023)
Based on the results of observations made during the PORPROV 2022 event, the researchers found a problem, namely when competing in the Kuburaya Regency petanque athletes made many mistakes when throwing pointing at long distances, namely where the distance of 8-9 meters the point where the shot fell was not right, causing many points to fail and benefited the opposing team a lot as a result of failed points. Therefore, the researcher was interested in taking the title